The effects of fenugreek seeds on the albino rat male reproductive system, MDA and SOD levels, and CD16 responses to Al2O3 NPs administration - Zainab Rasheed Hameed; Areej Zabbon; Genan Al-Bairuty (Acta Scientiarum. Animal Sciences, 2024)
Aluminum is widely distributed in the environment and enters the body via air, water, food, medications, and manmade objects. Some studies suggest that aluminum toxicity increases the rate of lipid peroxidation and consequently the generation of free radicals. However, the impact of nanoparticles on human health is still not fully understood. An indicator of lipid peroxidation in serum and tissues is an increased MDA. At the same time, there was a decrease in the level SOD and detection CD16 using the immunohistochemistry technique, objectives evaluating the impact of Al₂O₃ NPs on oxidative stress markers (MDA and SOD) and immune responses (CD16) in the testes, as well as the protective effects of fenugreek seed extract it was observed that these changes in levels recovered when given the plant extract of fenugreek seeds,65 albino rats were divided into 13 groups, including the control group Two concentrations of fenugreek extract (2 and 4 gm kg-1) and two concentrations of Al₂O₃ NPs solution (70 and 140 mg kg-1) were given orally to the rats for 21 and 35 days, respectively. The amino-histochemistry method was used to detect CD16, and its presence was checked along with the concentrations of oxidative stress markers like SOD and MDA. Immunohistochemical findings revealed a significant increase in CD16 in testicular cells; fenugreek extract doses significantly decreased MDA and slightly raised SOD. Al₂O₃ NPs. were shown to significantly raise MDA and decrease SOD at (p ≤ 0.05), according to the study's findings. and Immunohistochemical results detected a significant increase in CD16 in testicular cells, and doses of fenugreek extract reduced the MDA was significant, and a slightly significant increase in SOD. The study concluded Al₂O₃ NPs led to an imbalance in the testicle by generating oxidative stress and the fenugreek extract succeeded in alleviating the harmful effects of Al₂O₃ and by curbing MOD and strengthening the antioxidant defense system SOD, at the same time significantly influenced the histopathological and toxicological change responses through expression CD16.